Synthesis of N-Methyl-6-heterocyclic-1-oxoisoindoline Derivatives by Microwave Assisted Buchwald-Hartwig Amination - C. Kishor Kumar; H. Vijay Kumar; Nagaraja Naik (E-Journal of Chemistry)
An rapid and efficient microwave assisted Pd(II) catalyzed protocol for the preparation of N-methyl-6-heterocyclic-1-oxoisoindoline derivatives by Buchwald-Hartwig amination with an overall yield 68-85% has been described.